Hrvatska filozofkinja Ivana Rossi o filozofiji Henrija Bergsona - Skuhala Karasman, Ivana (2021)
Ivana Rossi (1892.–1963.) prva je Hrvatica koja je 1916. godine na Zagrebačkom sveučilištu doktorirala filozofiju tezom Osnovne misli filozofije Henri Bergsona. Profesionalno je radila kao gimnazijska profesorica. Objavila je dva rada: članak Nekoliko misli Henri Bergsona o estetici (1929.) i prijevod s engleskoga Peter Pan u perivoju Kensington (1922.). Ovdje donosim gotovo nepoznatu biografiju Ivane Rossi, sažetak njezine disertacije i pregled recepcije Bergsonove filozofije u nas.
The Croatian woman philosopher Ivana Rossi (1892–1963) was the first Croatian woman to defend a doctorate in philosophy in 1916 at the Faculty of Philosophy in Zagreb. The topic of her dissertation was "The Basic Thoughts of Henry Bergson"s Philosophy" (Osnovne misli filozofije Henri Bergsona). This dissertation was written much before Henri Bergson"s death in 1941, while he was professionally still very active. Ivana Rossi"s dissertation is the first serious presentation of Henri Bergson"s philosophical thought among the South Slavs. For hitherto unknown reasons — mostly likely personal — Ivana Rossi did not even attempt to work as a professional philosopher in the Academia. (She spent her entire professional career as a high school teacher in Zagreb, working in three different gymnasia: the "Kraljevska ženska realna gimnazija", the "Partizanska realna gimnazija", and the "III. muška realna gimnazija".) In 1929, she published the article, "Some of Henri Bergson"s Thoughts on Aesthetics" in the journal Književnik. Her second published work is her translation of James Barrie"s "Peter Pan in Kensington Park" published in 1922. This book is the first Croatian translation of a book on Peter Pan. In this article, in addition to the hitherto little–known biography of Ivana Rossi and the reception of Bergson"s philosophy in Croatia, the author also presents a summary of her dissertation.
Bibliografske bilješke uz tekst ; bibliografija i izvori: str. 481-482.
Sažetak ; Summary.
Keywords: Filozofkinje -- Biografija; Rossi, Ivana -- Bergson, Henri